(untitled) (Czech Journal of International Relations, 2024)
William Easterly: The Elusive Quest for Growth. Economists’ Adventures and Misadventures in the Tropics. 1st ed. Cambridge - Massachusetts - London: The Massachusetts Institute of Technology Press, 2002, 342 stran, ISBN 0-262-05065-X.